Northwest vs. Southeast: Factors Affecting the 1912 Suffrage Referendum Vote in Wisconsin - Hatfield, Julie (My University, 2008)
In 1911, the Wisconsin legislature passed a suffrage bill that would have allowed women in the state to vote in all elections, but to become a law it had to be voted on in a referendum. The Wisconsin Woman Suffrage Association and the Political Equality League campaigned potential voters the year prior to the referendum that was set for November 5, 1912, to persuade them to vote in favor of enacting the suffrage bill. The referendum was defeated due to multiple causal factors including ethnic and religious divisions, urban versus rural populations, brewing and agricultural industries, United States and Wisconsin politics, and voting patterns in Wisconsin prior to and during 1912. These factors interconnect to help explain why more northwestern counties voted in favor of suffrage versus southeastern counties where there was more suffrage organization.
Keywords: Women--Suffrage--Wisconsin--History.; Wisconsin Woman Suffrage Association.; Political Equality League (Wis.); Voting--Wisconsin--History.; Referendum--Wisconsin.; Suffrage--Law and legislation--Wisconsin.; Voting research--Wisconsin.